2016
DOI: 10.1128/jvi.01222-16
|View full text |Cite
|
Sign up to set email alerts
|

The Cytoskeletal Adaptor Obscurin-Like 1 Interacts with the Human Papillomavirus 16 (HPV16) Capsid Protein L2 and Is Required for HPV16 Endocytosis

Abstract: The human papillomavirus (HPV) capsid protein L2 is essential for viral entry. To gain a deeper understanding of the role of L2, we searched for novel cellular L2-interacting proteins. A yeast two-hybrid analysis uncovered the actin-depolymerizing factor gelsolin, the membrane glycoprotein dysadherin, the centrosomal protein 68 (Cep68), and the cytoskeletal adaptor protein obscurin-like 1 protein (OBSL1) as putative L2 binding molecules. Pseudovirus (PsV) infection assays identified OBSL1 as a host factor requ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
30
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 80 publications
(122 reference statements)
2
30
0
Order By: Relevance
“…(ii) The L2 protein may even span the TGN membrane twice, whereas both the N and C termini and the viral genome reside in the lumen during trafficking. Theoretically, this would allow for the L2 protein to interact with its cytosolic binding partners needed for intracellular trafficking preceding true translocation of the L2/DNA complex (29)(30)(31)(33)(34)(35)(36)(37), while at the same time allowing the carboxyl-terminal putative DNA binding domain on the luminal side to interact with viral genome. However, at the onset of mitosis, the carboxyl terminus has been shown by the Campos group to be accessible in the cytosol, suggesting that at this time the L2 protein assumes the possible type I transmembrane configuration previously suggested by us.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(ii) The L2 protein may even span the TGN membrane twice, whereas both the N and C termini and the viral genome reside in the lumen during trafficking. Theoretically, this would allow for the L2 protein to interact with its cytosolic binding partners needed for intracellular trafficking preceding true translocation of the L2/DNA complex (29)(30)(31)(33)(34)(35)(36)(37), while at the same time allowing the carboxyl-terminal putative DNA binding domain on the luminal side to interact with viral genome. However, at the onset of mitosis, the carboxyl terminus has been shown by the Campos group to be accessible in the cytosol, suggesting that at this time the L2 protein assumes the possible type I transmembrane configuration previously suggested by us.…”
Section: Discussionmentioning
confidence: 99%
“…During this time, data suggest that the L2 protein undergoes conformational changes resulting in translocation of the majority of the protein across the endosomal membrane through possible solo or concerted efforts of a membrane-destabilizing (residues 445 to 467) and a transmembrane-like (residues 45 to 65) domain (26)(27)(28)(29). This translocation event allows for the cytoplasmic region of the L2 protein (likely residues 65 to 473) to directly interact with cytoplasmic factors, most notably, the retromer complex, which facilitates the trafficking of the L2/DNA complex to the trans-Golgi network (TGN) (29)(30)(31)(32)(33)(34)(35)(36)(37). Residues 13 to 45 are located on the luminal side of transport vesicles, whereas residues 45 through 65 span the membrane.…”
mentioning
confidence: 99%
“…The virion is internalized by a previously unknown uptake pathway, which has the most commonalities with micropinocytosis resulting in the formation of HPV-harboring small, smooth endocytic vesicles (Schelhaas et al, 2012; Spoden et al, 2008; Spoden et al, 2013). Uptake does not depend on clathrin, caveolin, dynamin, or flotillin but requires reorganization of the actin cytoskeleton and may involve the cytoskeletal adaptor obscurin-like 1 (OBSL1) (Schelhaas et al, 2008; Schelhaas et al, 2012; Smith et al, 2008b; Wustenhagen et al, 2016). Activation of PI3 kinase has been implicated, likely participating in reorganization of the actin cytoskeleton during uptake (Fothergill and McMillan, 2006; Schelhaas et al, 2012; Surviladze et al, 2013).…”
Section: 2 Internalizationmentioning
confidence: 99%
“…C-terminal 40 amino acids of the HPV16 and HPV33 L2 protein have been shown to also interact with the dynein light chains DYNLT1 and DYNLT3, an interaction that seems to be important for nuclear delivery (Florin et al, 2006; Schneider et al, 2011). Recently, it was identified that obscurin-like 1 protein, a cytosolic cytoskeletal adaptor protein, forms complexes with the C-terminus of L2 (residues 280-473), which is important for efficient endocytosis (Wustenhagen et al, 2016). Currently, it is unknown precisely when the L2 protein becomes transmembranous.…”
Section: 1 Membrane Penetration and The L2 Proteinmentioning
confidence: 99%
“…Initial experiments showed that CD9 is involved after virus primary attachment to the cell surface and before capsid disassembly occurs. Inhibited CD63 colocalization as well as blocked capsid disassembly were both observed after CD9 knockdown and are strong indications of disturbed virus entry as also observed after depletion of other crucial entry mediators such as the annexin A2/S100A10 heterotetramer (A2t) [51], the obscurin-like protein OBSL1 [52], or the tetraspanin CD151 [13,14].…”
Section: Discussionmentioning
confidence: 79%